Geographies of affect: In search of the emotional dimension of place branding (Communication & Society, 2018)
Emotion is becoming one of the most important assets for the development of a strategy of place branding, with the primary aim of projecting competitive spatial identities through the use of brands. Despite this, few studies have focused on defining the role played by emotion in the affective connection that is established between people and places in the context of a place branding initiative. Consequently, the main goal of this article is to define a possible emotional dimension of place branding, by performing a meta-analysis and employing the contributions of emotional geography, environmental psychology and non-representational theory.